2010
DOI: 10.1111/j.1346-8138.2010.00939.x
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of a diet containing heat-killed Lactobacillus paracasei K71 on adult type atopic dermatitis

Abstract: The purpose of this study was to investigate the clinical effect of a supplementary diet containing heat-killed lactic acid bacterium Lactobacillus paracasei K71 (LAB diet) on adult patients with atopic dermatitis (AD). A randomized, double-blind, placebo-controlled study was conducted in 34 adult type AD subjects who were treated with conventional topical corticosteroid and tacrolimus. LAB diet or placebo was added over 12 weeks. The primary end-point was the clinical severity of AD which was evaluated by a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 30 publications
2
70
0
2
Order By: Relevance
“…A government-funded trial carried out in Japan by Moroi and colleagues 294 compared a once-daily dose of heat-killed Lactobacillus paracasei K71 for at least 12 weeks against placebo in 34 adults with mild to moderate eczema. There was no significant difference between the groups in change in eczema severity or change in itch scores or quality of life.…”
Section: Lactobacillus Paracasei K71 (Heat Killed)mentioning
confidence: 99%
See 2 more Smart Citations
“…A government-funded trial carried out in Japan by Moroi and colleagues 294 compared a once-daily dose of heat-killed Lactobacillus paracasei K71 for at least 12 weeks against placebo in 34 adults with mild to moderate eczema. There was no significant difference between the groups in change in eczema severity or change in itch scores or quality of life.…”
Section: Lactobacillus Paracasei K71 (Heat Killed)mentioning
confidence: 99%
“…Sixteen [289][290][291][292][293][294][295][296][297][298][299][300][301][302][303][304] new trials were reported after 2000. Nearly all of the 16 trials reported compared a probiotic against an inactive placebo or occasionally against no treatment.…”
Section: Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…W 8. i 12. tygodniu badania nasilenie zmian skórnych znacząco zmniejszyło się w grupie suplementowanej. Pacjenci z tej grupy zużywali także mniej leków działających miejscowo [56]. Matsumoto i wsp.…”
Section: Alergia Na Pokarmy -Leczenieunclassified
“…We recently found that intake of a dietary supplement containing heat-killed L. paracasei K71 was effective in reducing the clinical severity of atopic dermatitis in a randomized controlled trial [13], suggesting that this bacterial strain had immunomodulatory activity. Furthermore, a preliminary clinical study suggested that intake of L. paracasei K71 enhanced secretory immunoglobulin A (sIgA) release in the saliva (unpublished observation).…”
Section: Introductionmentioning
confidence: 99%